THE ROLE OF SWASH INFILTRATION IN DETERMINING THE BEACHFACE GRADIENT: A NUMERICAL STUDY - Masselink G.; Li L. (My University, 2001)
On sand and gravel beaches, the increase of the gradient of the beachface with increasing sediment size has been attributed to swash infiltration. The present study uses a process-based numerical model to examine in detail the role of swash infiltration in determining the beachface gradient. It is found that swash infiltration increases the onshore asymmetry in the swash flow, thereby enhancing onshore sediment transport and resulting in relatively steep beachface gradients. However, the accretionary effects of swash infiltration are only evident when the rate of infiltration is sufficiently large, i.e. when the total infiltration volume over a wave cycle exceeds c. 2% of the uprush volume. This threshold is attained when the hydraulic conductivity exceeds 1cm/s which is approximately equivalent to a grain size coarser than 1.5mm. This finding suggests that the correlation between beachface gradient and sediment size observed on sandy beaches is not due to enhanced swash asymmetry caused by swash infiltration. For gravel beaches, however, swash infiltration is likely to be the dominant factor in controlling the beachface gradient with increased hydraulic conductivity (i.e. sediment size) resulting in steeper beachface gradients.
Keywords: BEACHFACE; SWASH ZONE; SEDIMENT TRANSPORT; NUMERICAL MODELLING